Tragfähigkeit — ein unscharfer Schlüsselbegriff im Schnittpunkt von Raumordnung und Regional-Demographie - Weiß, Wolfgang (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
To the extent in which demographic change and selected resulting problems are considered in public, the specialist terms of demography are also losing their isolation. One such term is “carrying capacity”. Problematic are the multiple connotations with which the respective underlying problem is considered, often depending on the respective viewpoint. Like other terms it is moreover used in several disciplines and to top it all in colloquial language. This contribution understands itself as an attempt to explain carrying capacity from the perspective of regional demography, to establish linkages and also to follow a historical line. Remarkable is the variety of aspects of the term that can hardly be reconstructed but also its change in terms of content when it is occupied by political language following strategic objectives.